Exploring the benefits of cloud computing for sustainable construction in Nigeria - Oke, A.E. (Emerald Group Holdings Ltd., 2021)
Purpose: Cloud computing is one of the digitalization principles used in some sectors like banking, health and construction industry. This paper aims to examine the benefits of applying cloud computing for construction sustainability in Nigeria. Design/methodology/approach: The cloud computing benefits-related data were retrieved from previous studies and complemented with a questionnaire survey to obtain data from stakeholders involved in the execution of construction projects in Lagos State, Nigeria, through a convenient sampling technique. In addition, the relative importance index (RII) technique was used to investigate the acquired data. At the same time, analysis was accomplished using exploratory factor analysis (EFA). Findings indicated that numerous benefits could be derived by adopting cloud computing in the Nigerian construction industry. Findings: The findings from RII analysis showed the significant benefits of data storage ubiquity (i.e. location independence), high situational awareness, team collaboration, compatibility with advanced production facilities and improved project planning. Furthermore, the analysis of these benefits was conducted using EFA for the four construction maxims: construction productivity, back-office activities, design management and billing. Originality/value: This research illustrated the benefits of cloud computing in achieving a successful construction project. Besides, these findings are not only useful for achieving sustainable construction in Nigeria but also applicable to many developing countries. Â© 2021, Emerald Publishing Limited.